Ocular myasthenia gravis management - Kupersmith, Mark J.; Wolfe, Gil I.; Kaminski, Henry (Frontiers in Neurology, 2025)
Ocular myasthenia gravis (OMG) has no agreed-upon diagnostic and management criteria, leading to misdiagnoses and often misguided treatments. The purpose of this minireview is to provide guidance to clinicians who encounter possible OMG patients. We cite relevant literature and the recommendations for diagnosis and therapy based on the authors’ extensive experience in OMG. This report provides sound recommendations based on the authors’ successes and failures, coupled with relevant literature in the myasthenia gravis field.